Is Mindful Parenting Associated With Adolescents' Emotional Eating? The Mediating Role of Adolescents' Self-Compassion and Body Shame - Gouveia, Maria João Rosa (2018)
This study aimed to explore whether parents' mindful parenting skills were associated with adolescents' emotional eating through adolescents' levels of self-compassion and body shame. The sample included 572 dyads composed of a mother or a father and his/her child (12-18 years old), with normal weight (BMI = 5-85th percentile) or with overweight/obesity with or without nutritional treatment (BMI ≥ 85th percentile) according to the WHO Child Growth Standards. Parents completed self-report measures of mindful parenting (Interpersonal Mindfulness in Parenting Scale), and adolescents completed measures of self-compassion (Self-Compassion Scale-Short Form), body shame (Experience of Shame Scale), and emotional eating (Dutch Eating Behavior Questionnaire). Two path models, one with the total score for mindful parenting and the other with its dimensions, were tested in AMOS. Mindful parenting, specifically the dimension of compassion for the child, was indirectly associated with emotional eating through adolescents' self-compassion (point estimate = -0.27, p = 0.03, CI 95% [-0.61, -0.06]) and through self-compassion and body shame sequentially (point estimate = -0.19, p = 0.03, CI 95% [-0.37, -0.05]). The path model was invariant across weight groups but not across adolescents' sex (the indirect effects were significant among girls only). This study provides a novel comprehensive model of how mindful parenting, especially the dimension of compassion for the child, can be associated with adolescents' emotional eating behaviors by suggesting a potential sequence of mechanisms that may explain this association. This study suggests the beneficial effect of both mindful parenting and adolescents' self-compassion skills for adolescent girls struggling with feelings of body shame and emotional eating behaviors.